2021
DOI: 10.1161/strokeaha.120.033032
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy of Anterior Circulation Tandem Occlusions

Abstract: Background and Purpose: Endovascular therapy for tandem occlusion strokes of the anterior circulation is an effective and safe treatment. The best treatment approach for the cervical internal carotid artery (ICA) lesion is still unknown. In this study, we aimed to compare the functional and safety outcomes between different treatment approaches for the cervical ICA lesion during endovascular therapy for acute ischemic strokes due to tandem occlusion in current clinical practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Overall, although the need for intracranial revascularization is evident, the optimal approach for the treatment of extracranial occlusion is extreme uncertain. Emergent carotid artery stenting (eCAS) is often performed in the context of MT in cases with TO,9 10 even though its safety is unconfirmed. Additionally, the hemorrhagic risk related to periprocedural antithrombotic agents required for eCAS and the risk of early recurrent ischemic events of eCAS and the carotid artery angioplasty (CAA) or no carotid treatment are extremely variable in observational series 11–18…”
Section: Introductionmentioning
confidence: 99%
“…Overall, although the need for intracranial revascularization is evident, the optimal approach for the treatment of extracranial occlusion is extreme uncertain. Emergent carotid artery stenting (eCAS) is often performed in the context of MT in cases with TO,9 10 even though its safety is unconfirmed. Additionally, the hemorrhagic risk related to periprocedural antithrombotic agents required for eCAS and the risk of early recurrent ischemic events of eCAS and the carotid artery angioplasty (CAA) or no carotid treatment are extremely variable in observational series 11–18…”
Section: Introductionmentioning
confidence: 99%
“…We included acute ischemic stroke patients with AF, who were treated with ET and CAS. While retrospective data suggest a benefit of CAS in patients without AF treated with ET for tandem occlusions [ 23 , 24 ], evading stenting might be feasible especially in patients with AF. In this context, the results of randomized controlled trials (TITAN, EASI-TOC) will hopefully help determine the best approach.…”
Section: Discussionmentioning
confidence: 99%
“…Information on emergency extracranial ICA stenting due to dissection is limited to smaller observational studies and case reports. Most of the data have focused on endovascular strategies in tandem occlusions due to ICA dissection [223][224][225]. In a pooled analysis from registry data, emergent stenting in tandem occlusions has been suggested to be effective and safe, with a slight increase in mainly asymptomatic ICH [223,224].…”
Section: Dissection and Extracranial Bail-out Stentingmentioning
confidence: 99%
“…Most of the data have focused on endovascular strategies in tandem occlusions due to ICA dissection [223][224][225]. In a pooled analysis from registry data, emergent stenting in tandem occlusions has been suggested to be effective and safe, with a slight increase in mainly asymptomatic ICH [223,224]. Although both the anterograde and the retrograde approaches might be feasible, some authors have suggested a more conservative approach with stent placement only in cases of insufficient collateralization [225][226][227].…”
Section: Dissection and Extracranial Bail-out Stentingmentioning
confidence: 99%